The Case: "It's Like It's Not Her Anymore". (16th September 2016) - Unknown
Abstract : Ms. L. is a 31-year-old female who presents to Dr. Impf, a neurosurgeon. Ms. L. has a more than 25-year history of iteratively worsening Tourette syndrome, characterized by severe motoric and postural tics and respiratory expression (grunting). Ms. L. is a rather shy, somewhat introverted woman who spends her time with her husband and a small group of friends, mostly watching cooking shows. Although she has been, and is generally, a good student, she describes her academic performance as "not stellar." Following years of unsuccessful attempts at pharmacological therapy, Ms. L. was evaluated and accepted into an investigator-initiated research protocol (with provision for humanitarian care exemption) that Dr. Impf and her team were running for deep brain stimulation (DBS). During the neurosurgical procedure, electrodes were satisfactorily placed at bilateral subcortical targets (within the basal ganglia/striatum), and Ms. L. reported a reduced "urge to tic" and decreased frequency and severity of tics intraoperatively, immediately following surgery, during her recovery, and for 15 weeks following surgery. Then, however, the tics began to return and increased in frequency and progression, although not to the full preoperative extent. Attempts at altering DBS current parameters were not successful in reducing the severity and frequency of tics. Decreasing or terminating DBS current resulted in full rebound tics and respiratory expression, and Ms. L. finds this to be even more problematic than before (stating: "It's like I've felt a new way and don't want to go back to the other way"). Per definition, DBS did not achieve the desired medical/therapeutic outcomes.